Hand hygiene promotion delivered by change agents—Two attitudes, similar outcome. (13th March 2020) - Lee, Yew Fong; McLaws, Mary-Louise; Ong, Loke Meng; Amir Husin, Suraya; Chua, Hock Hin; Wong, See Yin; Pittet, Didier; Zingg, Walter
Abstract: Objective: To assess the effect of peer-identified change agents (PICAs) compared to management-selected change agents (MSCAs) on hand hygiene behavior in acute care. Design: Randomized-controlled study. Setting: Two internal medicine wards of a public, university-affiliated, tertiary-care hospital in Malaysia. Methods: We randomly allocated 2 wards to hand hygiene promotion delivered either by PICAs (study arm 1) or by MSCAs (study arm 2). The primary outcome was hand hygiene compliance using direct observation by validated auditors. Secondary outcomes were hand hygiene knowledge and observations from ward tours. Results: Mean hand hygiene compliance in study arm 1 and study arm 2 improved from 48% (95% confidence interval [CI], 44%–53%) and 50% (95% CI, 44%–55%) in the preintervention period to 66% (63%–69%) and 65% (60%–69%) in the intervention period, respectively. We detected no statistically significant difference in hand hygiene improvement between the 2 study arms. Knowledge scores on hand hygiene in study arm 1 and study arm 2 improved from 60% and 63% to 98% and 93%, respectively. Staff in study arm 1 improved hand hygiene because they did not want to disappoint the efforts taken by the PICAs. Staff in study arm 2 felt pressured by the MSCAs to comply with hand hygiene to obtain good overall performance appraisals. Conclusion: Although the attitude of PICAs and MSCAs in terms of leadership, mode of action and perception of their task by staff were very different, or even opposed, both PICAs and MSCAs effectively changed behavior of staff toward improved hand hygiene to comparable levels.